Length-weight relationship of 22 fish species (Osteichthyes) from the surf zone caught by seine net on the northern coast of Pernambuco - Brazil (Ocean and Coastal Research, 2022)
This study aims to analyze the length-weight relationship (LWR) of 22 fish species collected in the surf zone of Ponta de Pedras, northern coast of Pernambuco, Northeastern Brazil. The specimens were collected between August 2013 and July 2014 using a beach seine net, and their biometry were recorded in laboratory. The LWR was calculated using linear regression and, confidence intervals were estimated for the regression parameters a and b. A total of 1,433 specimens belonging to 22 species, 12 families, and six orders were collected. All species had b values within the expected range of 2.5-3.5 (except for S. plagusia). Additionally, 11 species have hyperallometry, eight have isometry, and three have hypoallometry. Herein, we present values of LWR for Lycengraulis grossidens, Trachinotus goodei, and Umbrina coroides, which are new to Northeastern Brazil, and Albula vulpes and Sparisoma radius which are new for the Brazilian coast.